Postoperative functioning of cardiac patients. Diagnostic methods of postoperative monitoring and risk of mortality - Gajos, Małgorzata; Włoszczyk, Patryk; Mioduska, Monika; Wałęsa, Grzegorz; Kujawska, Agnieszka; Androsiuk-Perkowska, Joanna; Perkowski, Radosław; Wnuk-Zaparucha, Agnieszka; Karczewska, Katarzyna; Bieniek, Daria; Husejko, Jakub; Skierkowska, Natalia; et al. (Journal of Education, Health and Sport, 2019)
AbstractIntroduction: Cardiovascular diseases are the most common reason for deaths of people. Progress in cardiac surgery and cardiac diagnosis a significantly decreased the risk of surgery and postoperative mortality in patients. The aim of our study was to present methods for monitoring patients after cardiac surgery and to assess the risk of morality.Material and methods: Articles in the EBSCO database have been analysed using keywords: postoperative functioning, cardiac surgery, risk of morality.Results: Studies have shown that cardiac surgery patients are a large group with many co-existing health problems that affect the occurrence of problems in the postoperative period.Hemodynamic monitoring of patients is carried out using a variety of techniques, both invasive and non-invasive. There are also many tools to assess post operative cognitive dysfunction.Interesting are modern methods of hemodynamic monitoring, which can be used by patients at home, after leaving the hospital. It should be remembered that all methods of treatment and monitoring of cardiac surgery patients have an impact on their quality of life and functioning. Do not forget about non-pharmacological methods of affecting the functioning of postoperative patients included in the ERAS protocol.Conclusions: Cardiac patients require a complex and interdisciplinary approach in the postoperative period. Many elements should be taken into account and prepared the patient for this situation. Progress in medicine more often reduces the risk of morality cardiac patients. However, should remember about the impact of all our activities on the quality of life and functioning of patients.Keywords: postoperative functioning, cardiac surgery, risk of moralityIntroductionCardiovascular diseases are causing more than 17 million deaths worldwide, and according to the World Health Organization (WHO) mortality due to cardiovascular diseases will become the leading cause of deaths of up to 20 million people per year [1]. Progress achieved in cardiac surgery and cardiac diagnosis allows for a significant reduction in the risk of surgery and postoperative mortality in patients. However, the evaluation of the result of the operation should not focus only on the effectiveness of the surgery itself. Treatment of cardiac surgery patients should also take into account how will they function in everyday life situations after the surgery.